Assessment of Land Characteristics and Suitability for Citrus Development in Dry Land Punung, Pacitan Regency - Supriyadi Supriyadi; Rahayu Rahayu; Ganjar Herdiansyah; Aktavia Herawati; Dita Risky Novianti (JOURNAL OF TROPICAL SOILS, 2024)
One of the Indonesian provinces where the agricultural industry drives the economy is Punung, Pacitan, which has local conditions that are particularly suitable for producing citrus, giving this product the potential to continue to expand in popularity. Land evaluation tries to provide information on its potential for a particular purpose. This research was conducted to know land suitability classes, limiting factors, and improvement efforts that can be made. This research is exploratory descriptive with a variable approach through field survey and using a purposive random sampling method based on Land Mapping Units. Data analysis was carried out using the matching method between land characteristics and conditions for growing citrus, a statistical test by ANOVA (Analysis of Variance), and Duncan’s Multiple Range Test (DMRT) to find the factors that most determine land characteristics in Punung. The study results show that the actual land suitability class in Punung is marginally suitable. Improvements that can be made to increase the availability of nutrients in the soil in the form of available P2O5 with a low level of management is to apply P fertilization according to the needs of citrus. ANOVA results proved that the variety of soil types significantly influences some of the land characteristics.